Comparative effectiveness of school‐based interventions targeting physical activity, physical fitness or sedentary behaviour on obesity prevention in 6‐ to 12‐year‐old children: A systematic review and meta‐analysis. (19th January 2021) - Podnar, Hrvoje; Jurić, Petra; Karuc, Josip; Saez, Marc; Barceló, Maria A.; Radman, Ivan; Starc, Gregor; Jurak, Gregor; Đurić, Saša; Potočnik, Žan Luca; Sorić, Maroje
Summary: A systematic search of the literature was performed to compare the effects of interventions that targeted sedentary behaviours or physical activity (PA) or physical fitness on primary prevention of obesity in 6‐ to 12‐year‐old children. The search identified 146 reports that provided relevant data for meta‐analysis. Point estimates in % body fat were higher for fitness interventions compared with PA interventions (standardized mean difference = −0.11%; 95% CI = −0.26 to 0.04, and −0.04%; 95% CI = −0.15 to 0.06, respectively). Including sedentary behaviour to a PA‐ or fitness‐oriented intervention was not accompanied by an increase in intervention effectiveness, as the point estimates were slightly smaller compared with those for PA‐ or fitness‐only interventions. Overall, the effects tended to be larger in girls than in boys, especially for PA + sedentary behaviour interventions. There was some evidence for inequality, as the effects on body mass index were seen when interventions were delivered in the general population (standardized mean difference = −0.05, 95% CI = −0.07 to −0.02), but not in groups of disadvantaged children (standardized mean difference = −0.01, 95% CI = −0.29 to 0.19). In conclusion, school‐based PA interventions appear to be an effective strategy in the primary prevention of childhood obesity among 6‐ to 12‐year‐old children, but targeting sedentary behaviour in addition to PA or fitness does not increase the effectiveness of the intervention.